Sing out! [Bladmuziek]. - Sing Out Corporation (Hamburg : Sing Out Corporation, 1985)
Deze brochure bevat volgende liederen
Auld Lang Syne
Fine Flowers in The Valley
What's Happening
Birthday Cake
Dust My Broom
Drop Down Mama
Barstow
Testimony
The Return
Artifical Means
No Más!
Steppin' Out
Appleseeds
Precious Friend (You will be there)
You Say The Ballte Is Over
One Kind Favor
Banty Rooster
Just An Old Women
The Gooey-Duck Song
Ascending Woman
Gypsy
The Color Song
Your Daughters And Your Sons
Engels
Bladmuziek
Keywords: Redpath, Jean; Hammond, John; Ferron; Reno, Don; Jarell, Tommy; liederen; partituren